2017
DOI: 10.1002/sctm.17-0071
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Stem Cells Alter Gene Expression and Improve Healing of Distal Limb Wounds in Horses

Abstract: Distal extremity wounds are a significant clinical problem in horses and humans and may benefit from mesenchymal stem cell (MSC) therapy. This study evaluated the effects of direct wound treatment with allogeneic stem cells, in terms of gross, histologic, and transcriptional features of healing. Three full‐thickness cutaneous wounds were created on each distal forelimb in six healthy horses, for a total of six wounds per horse. Umbilical cord‐blood derived equine MSCs were applied to each wound 1 day after wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…This outcome was not anticipated by the authors because it has been reported that occlusive dressings potentially decrease the risk for wound infection . Moreover, bandage changes in previous equine distal limb wound healing studies ranged from one to three times per week, and no evidence of wound infection was reported during these trials . The exact cause of infection in this study remains unknown.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This outcome was not anticipated by the authors because it has been reported that occlusive dressings potentially decrease the risk for wound infection . Moreover, bandage changes in previous equine distal limb wound healing studies ranged from one to three times per week, and no evidence of wound infection was reported during these trials . The exact cause of infection in this study remains unknown.…”
Section: Discussionmentioning
confidence: 61%
“…[69][70][71] Moreover, bandage changes in previous equine distal limb wound healing studies ranged from one to three times per week, and no evidence of wound infection was reported during these trials. [6][7][8][9][10][11][12][13] The exact cause of infection in this study remains unknown. An additional flaw in histologic processing further eliminated a control wound, reducing our total number of wounds to be examined from 32 to 28.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The potential use of allogeneic MSCs for the treatment of various diseases has also been piloted, including humans and horses, for instance, for indications such as cardiac damage post-myocardial infarction and wound healing (26,27). However, whilst long-term safety data is still very sparse, evidence is now emerging on a convincing safety profile for the use of allogeneic MSCs in cardiac regeneration (28) and autoimmune disease in man (29) as well as in osteoarthritis in horses (30).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are numerous delivery systems such as: natural biological vehicles (such as bacteria and viruses [1,2], various cell types including red blood cells (RBCs) [3][4][5], immune cells [6,7], stem cells [8][9][10][11] and manufactured carriers (liposomes [12], micelle [13], polymeric capsules [14][15][16][17], polymeric complexes [18][19][20][21]). Polymeric nanocapsules (NCs) are a promising system of natural carriers for targeted drug delivery because of their low cytotoxicity, shell flexibility, and high in vivo stability [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%